IDO1 inhibition potentiates vaccine-induced immunity against pancreatic adenocarcinoma - Alex B. Blair; Jennifer Kleponis; Dwayne L. Thomas II; Stephen T. Muth; Adrian G. Murphy; Victoria Kim; Lei Zheng (The Journal of Clinical Investigation, 2019)
Pancreatic ductal adenocarcinoma (PDAC) represents an immune quiescent tumor that is resistant to immune checkpoint inhibitors. Previously, our group has shown that a GM-CSF–secreting allogenic pancreatic tumor cell vaccine (GVAX) may prime the tumor microenvironment by inducing intratumoral T cell infiltration. Here, we show that untreated PDACs express minimal indoleamine-2,3-dioxygenase (IDO1); however, GVAX therapy induced IDO1 expression on tumor epithelia as well as vaccine-induced tertiary lymphoid aggregates. IDO1 expression plays a role in regulating the polarization of Th1, Th17, and possibly T regulatory cells in PDAC tumors. IDO1 inhibitor enhanced antitumor efficacy of GVAX in a murine model of PDACs. The combination of vaccine and IDO1 inhibitor enhanced intratumoral T cell infiltration and function, but adding anti–PD-L1 antibody to the combination did not offer further synergy and in fact may have had a negative interaction, decreasing the number of intratumoral effector T cells. Additionally, IDO1 inhibitor in the presence of vaccine therapy did not significantly modulate intratumoral myeloid-derived suppressor cells quantitatively, but diminished their suppressive effect on CD8+ proliferation. Our study supports the combination of IDO1 inhibitor and vaccine therapy; however, it does not support the combination of IDO1 inhibitor and anti–PD-1/PD-L1 antibody for T cell–inflamed tumors such as PDACs treated with vaccine therapy.